Recent insights into the molecular genetics of dementia - Rademakers, Rosa (2009)
Our understanding of the molecular genetic basis of two common neurodegenerative dementias, Alzheimer’s disease (AD) and frontotemporal lobar degeneration (FTLD) has greatly advanced in recent years. Progranulin mutations were identified as a major cause of FTLD and a potential susceptibility factor for other forms of dementia. In addition, through copy-number analyses of previously identified disease genes and the study of microRNA regulation in dementia, new evidence emerged to support the view that subtle variability in the expression of known disease proteins may increase the risk for sporadic forms of dementia. Finally, in late-onset AD populations, the first genome-wide association studies were performed and novel potential AD susceptibility genes reported. These exciting findings provide novel insights into the disease mechanisms underlying dementia and hold promise for the development of potential treatments.